Amorphous structure in Cu-Zn-V-Al oxide composite catalyst for methanol reforming - Mohd Sabri, Mahmud; Zahira, Yaakob; Abu Bakar, Mohamad; Wan Ramli, Wan Daud; Vo, Dai-Viet N. (IIUM, Malaysia, 2018)
Cu-Zn-V-Al oxide composite catalysts were prepared using a co-precipitation method to investigate hydrogen and carbon monoxide yield of a methanol reforming reaction. The mass compositions of metals were initially determined on the Simplex Centroid statistical design. The effects of various metal compositions on the physicochemical properties of the catalyst were studied via X-ray diffractogram (XRD), temperature-programmed reduction (TPR) analyses, and reaction. XRD revealed crystals in the samples. Crystalline CuO in Cu30V30Al40 formed with the addition of zinc oxide at the metal loading below 30 wt%. A combination of zinc oxide and vanadia, however, had no Zn-V complex crystal but its scanning electron microscopy image showed the formation of string structures (AS). The catalyst that contained the AS exhibited a broad hydrogen reduction peak in the TPR analysis. Vanadium at a loading below 40 wt% with various zinc and cuprum compositions also formed small ASs and exhibited single TPR peaks. A reaction yield study revealed the optimum compositions of metal oxides when the data was fitted by response surface plots. The catalysts with high content of AS were not at the peaks however. Cu-Zn based catalysts showed the highest hydrogen yield for the reaction temperature of between 150 oC to 225 oC and vanadia-promoted catalyst with AS only appeared to be the optimum catalyst at the higher temperature.